A current landscape of specific learning disability identification: Training, practices, and implications. Issue 1 (28th October 2018) - Maki, Kathrin E.; Adams, Sarah R.
Abstract: Specific learning disability (SLD) identification procedures vary across states (Maki et al., 2015, School Psychol Quart, 30, 457–469); however, the extent to which SLD identification methods are implemented at the district level is not well understood. Moreover, the high‐stakes nature of SLD identification necessitates extensive training, but research regarding graduate and postgraduate training in SLD is limited. This study examined school psychologists' SLD training and practices through survey methodology. Results showed that a growing number of school psychologists use, prefer, and receive training in response to intervention and pattern of strengths and weaknesses to identify students with SLD while the use of and preference for ability–achievement discrepancy may be decreasing. However, nearly one‐third of school psychologists still reported the use of ability–achievement discrepancy. In addition, over half of school psychologists reported using state department of education guidance documents to inform their SLD identification practices. Implications for training and practice are discussed.